Advertisements
Advertisements
Question
Solution
\[\int\left( \frac{3 + 4x - x^2}{x^2 - x + 2x - 2} \right)dx\]
\[ = \int\left( \frac{- x^2 + 4x + 3}{x^2 + x - 2} \right)dx\]
\[\frac{- x^2 + 4x + 3}{x^2 + x - 2} = - 1 + \frac{5x + 1}{x^2 + x - 2} .............(1)\]
\[ \therefore \frac{5x + 1}{x^2 + x - 2} = \frac{5x + 1}{x^2 + 2x - x - 2}\]
\[ = \frac{5x + 1}{x\left( x + 2 \right) - 1\left( x + 2 \right)}\]
\[\text{Let }\frac{5x + 1}{\left( x - 1 \right)\left( x + 2 \right)} = \frac{A}{x - 1} + \frac{B}{x + 2}\]
\[ \Rightarrow \frac{5x + 1}{\left( x - 1 \right)\left( x + 2 \right)} = \frac{A\left( x + 2 \right) + B\left( x - 1 \right)}{\left( x - 1 \right)\left( x + 2 \right)}\]
\[ \Rightarrow 5x + 1 = A\left( x + 2 \right) + B\left( x - 1 \right) ..........(2)\]
\[\text{Putting }x + 2 = 0\text{ or }x = - 2\text{ in eq. (2)}\]
\[ \Rightarrow 5x - 2 + 1 = A \times 0 + B\left( - 2 - 1 \right)\]
\[ \Rightarrow B = 3\]
\[\text{Putting }x - 1 = 0\text{ or }x = 1\text{ in eq. (2)}\]
\[ \Rightarrow 5 \times 1 + 1 = A\left( 3 \right) + B \times 0\]
\[ \Rightarrow A = 2\]
\[ \therefore \frac{5x + 1}{\left( x - 1 \right)\left( x + 2 \right)} = \frac{2}{x - 1} + \frac{3}{x + 2} ............(3)\]
From (1) and (3)
\[\frac{- x^2 + 4x + 3}{x^2 + x - 2} = - 1 + \frac{2}{x - 1} + \frac{3}{x + 2}\]
\[ \Rightarrow \int\frac{- x^2 + 4x + 3}{x^2 + x - 2}dx = \int - 1 dx + \int\frac{2}{x - 1}dx + \int\frac{3}{x + 2} dx\]
\[ = - x + 2 \ln\left( x - 1 \right) + 3 \ln\left( x + 2 \right) + C\]
APPEARS IN
RELATED QUESTIONS
If f' (x) = x − \[\frac{1}{x^2}\] and f (1) \[\frac{1}{2}, find f(x)\]
\[\int\left( e^\text{log x} + \sin x \right) \text{ cos x dx }\]
Evaluate the following integral:
If \[\int\frac{1}{\left( x + 2 \right)\left( x^2 + 1 \right)}dx = a\log\left| 1 + x^2 \right| + b \tan^{- 1} x + \frac{1}{5}\log\left| x + 2 \right| + C,\] then
\[\int {cosec}^4 2x\ dx\]